A MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN BERBANTUAN PEMBELAJARAN TEMATIK TERPADU BERNUANSA MODEL INTERACTIVE-COMPENSATORY. - Ryan Dwi Puspita; Rahman ` (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2017)
ABSTRACT Based on the preliminary study, it revealed that the 5th grade students in some elementary schools in Bandung Regency had low ability to perform reading comprehension. This can be seen from students’ low ability to express explicit meanings, define main idea, search for keywords, retell the contents of the text with their own words, create a concept map, and understand the message of the author. Based on this finding, there is a need to develop instructional devices based on specific learning models to improve reading comprehension. The purpose of this study was to examine the effect of using integrated thematic instructional based on Interactive-Compensatory Model (ICM) to improve reading comprehension among 5th grade students. This study applied quasi-eksperiment method. This study used sample of 123 students of 5th graders in 2 elementary schools. The results of this study show that the use of instructional based on ICM had significant effect on improving reading comprehension of informational text among grade 5 elementary school students. This was evidenced by the difference of students’ reading comprehension ability before and after learning by using thematic and integrated instructional based on ICM. Keywords: Interactive-Compensatory Model, Instructional Integrated and Thematic, Reading Comprehension ABSTRAK Hasil observasi menunjukkan siswa kelas 5 di beberapa sekolah dasar di Kabupaten Bandung memiliki kemampuan membaca pemahaman yang lemah. Hal ini ditunjukkan dengan rendahnya kemampuan siswa dalam mengungkapkan makna yang tersurat, menentukan pokok pikiran, mencari kata kunci, menceritakan kembali isi teks dengan kata-kata sendiri, membuat peta konsep, dan memahami pesan penulis. Berdasarkan data ini, maka diperlukan pengembangan perangkat pembelajaran berbasis model pembelajaran khusus untuk meningkatkan kemampuan membaca pemahaman. Tujuan penelitian ini untuk menguji pengaruh penggunaan perangkat pembelajaran tematik terpadu berbasis model Interactive-Compensatory untuk meningkatkan kemampuan membaca pemahaman siswa kelas 5 sekolah dasar. Penelitian ini menggunakan metode eksperimen kuasi. Penelitian ini menggunakan sampel 123 siswa kelas 5 di dua sekolah dasar . Hasil penelitian ini menunjukkan bahwa penggunaan pembelajaran tematik terpadu bernuansa model Interactive-Compensatory berpengaruh signifikan pada peningkatan kemampuan membaca pemahaman teks informasi siswa kelas 5 sekolah dasar. Hal ini dibuktikan dengan adanya perbedaan kemampuan membaca pemahaman siswa pada saat sebelum dan pada saat sesudah pembelajaran dengan menggunakan pembelajaran tematik terpadu bernuansa model Interactive-Compensatory. Kata Kunci: Membaca Pemahaman, Pembelajaran Tematik Terpadu, Model Interactive-Compensatory.